New for Ukraine species of lichens and lichenicolous fungi from marl limestones in the Northern Black Sea Region - Khodosovtsev, O.Ye.; Darmostuk, V.V. (Український ботанічний журнал, 2018)
During the recent field season, we focused on lichens and lichenicolous fungi of petrophytic steppe habitats. They are widespread within the Black Sea Lowland in Ukraine. The marl limestones and pure limestone pebbles are outcropped in the central parts of the steppe slopes. The stone surfaces are colonized by pioneer lichen communities where endolithic life forms are mostly imperceptible. The petrophytic steppe habitats are protected in Europe. Six new for Ukraine species of lichens and two species of lichenicolous fungi from these habitats are reported in the article. A lichenicolous fungus, Acaroconium punctiforme, is characterized by subglobose black pycnidia, ampuliform conidiogenous cells, enteroblastic broadly ellipsoid aseptate pale brown conidia and Sarcogyne regularis as a host. Aspicilia subfarinosa has chalky-white thallus with farinose, smooth surface with occasional small cracks. The lichenicolous fungus Lichenochora wasseri s. l. was found on Xanthocarpia lactea. It is a new host for this lichenicolous fungus. Psorotichia montinii has minutely areolate thin crustose to almost powdery blackish thallus, minute invisible apothecia with punctiform discs. Verrucaria bernaicensis is characterized by pale gray, epruinose, areolate or subsquamulose thallus, immersed perithecia, lacking involucrellum, and small ellipsoid ascospores. Verrucaria papillosa differs from V. viridula by its completely endolytic thallus and undeveloped involucrellum. Verrucaria schindleri is similar to V. muralis, but has dark exciple in the lower part. The localities in Ukraine, ecology and distribution data for the new records are provided. Протягом останнього польового сезону досліджували лишайники і ліхенофільні гриби в петрофітних степових біотопах. Вони поширені в межах Причорноморської низовини, де в середній частині степових схилів вимиваються вапнякові та мергелисті камінці. Згодом їх колонізують піонерні лишайникові угруповання, де переважають ендолітні життєві форми. Комплекс петрофітих степових біотопів охороняється в Європі. У статті представлена інформація щодо знахідок шести нових для України видів лишайників і двох видів ліхенофільних грибів, знайдених в цих біотопах. Ліхенофільний гриб Acaroconium punctiforme характеризується субглобулярними чорними пікнідами, ампулоподібними конідіогенними клітинами, ентеробластичними широкоеліпсоїдними несептованими блідо-коричневими конідіями і зростає на Sarcogyne regularis. Лишайник Aspicilia subfarinosa має одноманітно-накипну білу слань з гладкою поверхнею і нерегулярними дуже дрібними тріщинками. Ліхенофільний гриб Lichenochora wasseri s. l. був виявлений на Xanthocarpia lactea, який є його новим господарем. Psorotichia montinii утворює дуже тонку, чорну слань, дрібні непомітні апотеції з точкоподібним диском. Verrucaria bernaicensis характеризується блідо- сірою, ареольованою, сланню, зануреними перитеціями і невеликими еліпсоїдними аскоспорами. Verrucaria papillosa відрізняється від V. viridula повністю ендолітною сланню і нерозвиненим вкривальцем, V. schindleri схожий на V. muralis, але має темний ексціпул у нижній частині. У статті також наведено всі місцезнаходження знайдених видів, їхні екологічні особливості та поширення в світі. В течение последнего полевого сезона изучали лишайники и лихенофильные грибы в петрофитных степных биотопах. Они распространены в пределах Причерноморской низменности, где в средней части степных склонов вымываются известняковые и мергелистые камешки. Со временем их колонизируют пионерные лишайниковые сообщества, где преобладают эндолитные жизненные формы. Комплекс петрофитных степных биотопов охраняется в Европе. В статье представлена информация о находках шести новых для Украины видов лишайников и двух видов лихенофильных грибов, найденных в этих биотопах. Лихенофильный гриб Acaroconium punctiforme характеризуется субглобулярными чёрными пикнидами, ампулообразными конидиогенными клетками, энтеробластическими широкоэллипсоидными несептированными бледно-коричневыми конидиями и произрастанием на Sarcogyne regularis. Лишайник Aspicilia subfarinosa имеет однообразно накипное белое слоевище с гладкой поверхностью и случайными очень мелкими трещинками. Лихенофильный гриб Lichenochora wasseri s. l. был обнаружен на Xanthocarpia lactea, который является его новым хозяином. Psorotichia montinii образует очень тонкое, черное слоевище, мелкие незаметные апотеции с точковидным диском. Verrucaria bernaicensis характеризуется бледно-серым, ареолированным, слоевищем, погруженными перитециями и небольшими эллипсоидными аскоспорами. Verrucaria papillosa отличается от V. viridula полностью эндолитным слоевищем и неразвитым покрывальцем, V. schindleri похож на V. muralis, но имеет темный эксципул в нижней части. В статье также приведены все местонахождения найденных видов, экологические особенности и распространение в мире.